2019
DOI: 10.2147/cmar.s221110
|View full text |Cite
|
Sign up to set email alerts
|

<p>Malignant Triton Tumor in a Child: Case Report and Literature Review</p>

Abstract: Malignant triton tumor (MTT) is a rare and devastating malignant peripheral nerve-sheath tumor, which shows rapid growth and poor clinical outcomes. Here, we reported a 2-year-old girl who was diagnosed as MTT, an overview of the literature was conducted to discuss the clinical features and optimal treatment strategies of MTT. Methods: We conducted an analysis of 42 patients from the PubMed, Medline, Embase and Web of Science databases for relevant articles published between 1938 and 2018. Results: A 2-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A range of cases presentation in the literature we reviewed describe the imaging manifestations (including CT and MRI) correlated with MTT: giant lump, heterogeneity, irregular margins, intratumoral hemorrhage, necrosis, lobulation, calcifications, heterogenous enhancement on postcontrast CT or MRI, hypointense/isointense T1WI and hyperintense T2WI signal on MRI, and diffusion restriction on DWI and ADC 1,8–32,39,40 . Zain et al 20 and Li et al 29 had reported similar conclusions, Li et al pointed out some characteristics common to MTTs and MPNSTs, including ill‐defined margin, intratumoral lobulation, peripheral edema, calcifications, and destruction of adjacent bone tissues.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A range of cases presentation in the literature we reviewed describe the imaging manifestations (including CT and MRI) correlated with MTT: giant lump, heterogeneity, irregular margins, intratumoral hemorrhage, necrosis, lobulation, calcifications, heterogenous enhancement on postcontrast CT or MRI, hypointense/isointense T1WI and hyperintense T2WI signal on MRI, and diffusion restriction on DWI and ADC 1,8–32,39,40 . Zain et al 20 and Li et al 29 had reported similar conclusions, Li et al pointed out some characteristics common to MTTs and MPNSTs, including ill‐defined margin, intratumoral lobulation, peripheral edema, calcifications, and destruction of adjacent bone tissues.…”
Section: Discussionmentioning
confidence: 71%
“…We compiled data on reported cases of MTT in the recent 6 years (2018–2023, Table 1). 1,6–38 There were totally 37 cases with a mean age of 39.4 years (range 8 months old–75 years old), including 24 male and 13 female patients. Eleven cases originated in the abdomen (30%), 10 cases in the head and neck (27%), 8 cases in the thoracic cavity (21%), 6 cases in the limbs (16%), 1 case in the spine (3%), and 1 case in the buttocks (3%).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Malignant triton tumor is an extremely rare variant of the MPNSTs with rhabdomyosarcomatous differentiation, typically found on the head, neck, extremities, and trunk, and there are case reports that have shown this tumor growing in places such as the nasal cavity, paranasal sinus, lumbar spine, parapharyngeal space, rectum, mediastinum, palate, tibial nerve, esophagus, cerebellopontine angle, and acoustic nerve. It rarely affects the kidney, brain, buttock, retroperitoneum, thoracic spine, pelvis, genitourinary tract, and thigh [1] , [2] , [3] , [5] , [7] , [14] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…MTT is manifested as a mass that may or may not be painful. Regarding the estimated 5-year survival rate, studies have shown a variation between 5 and 20% for MTT [2] , [12] , [13] and 34–60% for MPNST [12] , [13] , and the morbidity rates of MTT are equal for both sexes [14] . However, the forms associated with NF1 are more commonly found in men and children, while sporadic forms have a higher incidence in women and older individuals [11] .…”
Section: Introductionmentioning
confidence: 99%
“…It commonly arises from a peripheral nerve in the neck, extremities or trunk, while it is rarely found in the cranial temporal and parietal fossa, viscera, mediastinum and retroperitoneum (1). Recently, Dias et al (cited in Zhao et al) (2) have reported an uncommon case of cerebral MTT in Brazil. In addition, most MTT cases are reported in adults.…”
Section: Introductionmentioning
confidence: 99%